Proper efficiency conditions and duality models for nonsmooth multiobjective fractional programming problems with operator constraints, Part II: Applications - Zalmai G.J. (Utilitas Mathematica, 1997)
This paper discusses the relevance and applicability of the abstract proper efficiency-duality theory developed in a companion paper to several important classes of nonsmooth multiobjective fractional optimization problems with operator constraints. These include constrained optimal control problems with and without arbitrary norms and square roots of positive semidefinite quadratic forms, constrained problems in the calculus of variations involving arbitrary norms and square roots of positive semidefinite quadratic forms, problems involving nonsmooth integral functionals, semiinfinite programming problems, problems containing discrete and continuous max functions, problems containing support functions, and simultaneous best approximation problems.